Digital Citizenship Practices and Implementation of Learning Modalities in the Higher Education Institutions under the New Normal in General Santos City - Okoye, Anthony (JPAIR Institutional Research, 2024)
While the shift to technology-mediated learning in higher education has been widely documented, less is known about the interplay between digital citizenship practices within institutions, particularly in Mindanao. One of the means to address this gap is by investigating the relationship between these two factors within higher education institutions in General Santos City. While some argue that technological infrastructure and pedagogical innovation are sufficient for effective online and blended learning, this study posits that a strong foundation of digital citizenship is essential for maximizing the benefits of these modalities. Specifically, the research examined four key elements of digital citizenship: digital identity, digital netiquette, digital footprint, and digital privacy, alongside the implementation of learning modalities across curriculum development, supervision of instruction, faculty development, and research and extension services. Data were collected through a structural survey questionnaire. Findings revealed a high level of digital citizenship practices and a very satisfactory implementation of learning modalities. The data indicate that students and teachers alike are well-versed in digital ethics, demonstrating awareness of online safety protocols and responsible internet behaviors. This strong foundation in digital citizenship can be leveraged to develop further the critical thinking and information literacy skills required for navigating the digital landscape of the 21st century. Furthermore, a significant positive relationship was observed between these two factors across all domains. This suggests that strong digital citizenship within HEIs contributes to a more effective adaptation to a technology-driven educational environment.
Keywords: Digital Citizenship; Learning Modalities; Higher Education Institutions; General Santos City; Mindanao; Philippines